Case report: Use of 68Ga-DOTATATE-PET for treatment guidance in complex meningioma disease - Meißner, Anna-Katharina; von Spreckelsen, Niklas; Al Shughri, Abdulkader; Brunn, Anna; Fuertjes, Gina; Schlamann, Marc; Schmidt, Matthias; Dietlein, Markus; Rueß, Daniel; Ruge, Maximilian I.; Galldiks, Norbert; Goldbrunner, Roland (Frontiers in Oncology, 2022)
Currently, contrast-enhanced MRI is the method of choice for treatment planning and follow-up in patients with meningioma. In addition, PET imaging of somatostatin receptor 2 (SSTR2) expression using 68Ga-DOTATATE may provide a higher sensitivity for meningioma detection, especially in cases with complex anatomy or in the recurrent setting. Here, we report on a patient with a multilocal recurrent atypical meningioma, in which 68Ga-DOTATATE PET was considerably helpful for treatment guidance and decision-making.